The Paradigm of Recognition : Freedom as Overcoming the Fear of Death. - Cobben, Paul (Critical studies in German idealism., 2012)
In The Paradigm of Recognition. Freedom as Overcoming the Fear of Death Paul Cobben elaborates a paradigm of recognition based on Hegel's Phenomenology of Spirit. This framework enables fundamental criticism of Honneth's three forms of social freedom.